Nitrogenous Fertilizer Coated With Zinc Improves the Productivity and Grain Quality of Rice Grown Under Anaerobic Conditions - Wahid, Muhammad Ashfaq; Irshad, Muhammad; Irshad, Sohail; Khan, Shahbaz; Hasnain, Zuhair; Ibrar, Danish; Khan, Afroz Rais; Saleem, Muhammad Farrukh; Bashir, Saqib; Alotaibi, Saqer S.; Matloob, Amar; Farooq, Naila; et al. (Frontiers in Plant Science, 2022)
Ample quantity of water and sufficient nutrients are required for economical rice production to meet the challenge of ever increasing food demand. Currently, slow release nitrogenous fertilizers for efficient inputs utilization and to gain maximum economic yield of field crops are in the limelight for researchers and farmers. In this study, we have evaluated the comparative efficacy of conventional urea and coated urea (zinc and neem) on rice production grown under aerobic and anaerobic regimes in the greenhouse conditions. For imposition of aerobic regime, field capacity was maintained at 80-100% to keep the soil aerated. On the other hand, in the case of anaerobic regime, pots were covered with a polythene sheet throughout the course of experimentation to create the flooded conditions. All forms of urea either conventional or coated (zinc and neem) improved plant growth, gas exchange, yield and yield contributing parameters and quality characteristics of rice crop but higher increment in all attributes was found in case of zinc coated urea. Gas exchange attributes (photosynthetic rate; 30% and stomatal conductance; 24%), yield parameters like plant height (29%), tillers per plant (38%), spikelets per spike (31%), grains per panicle (42%), total biomass (53%) and grain yield (45%) were recorded maximum in rice plants treated with zinc coated urea. Highest grain and straw nitrogen contents, grain protein contents and grain water absorption ratio were also found in plants under zinc coated urea application. Regarding irrigation practices, anaerobic regime was found more responsive as compared to aerobic regime regarding rice growth, productivity and quality traits. Thus, to enhance the productivity and quality of rice grown in anaerobic conditions, application of zinc coated urea will be more responsive as compared to other forms of urea applied.